Role of Magnetic Resonance Imaging in the Diagnosis of Placenta Accreta - Niu, Lei; Cui, Wen; Zhu, Chunxia; Lu, Xiaoning; Wang, Yongkang; Wang, Feng (Current Medical Imaging, 2024)
Introduction To analyze the value of magnetic resonance imaging (MRI) in suspicious cases for prenatal detection of placenta accreta (PA). Materials and Methods A total of 50 placental MRI exams performed on a 1.5T scanner were retrospectively reviewed by two radiologists in consensus. HASTE (half-Fourier acquisition single-shot turbo spin echo)and True-FISP (true fast imaging with steady-state precession) sequences were acquired. Findings from MRI were compared with the final diagnosis, which was determined by clinical findings at delivery and pathological examination of specimens. Results Of 50 pregnant women in the analysis, 33 required cesarean hysterectomy, and 17 underwent cesarean delivery.MRI signs such as myometrial thinning, loss of T2 hypointense interface(loss of retroplacental clear space on US), heterogenous intraplacental sign, and intraplacental T2 dark bands were more likely to be seen in this group. In this group, the cases that were finally clinically and pathologically confirmed were 12, 16, and 22 cases of placenta accreta vera, placenta increta, and placenta percreta respectively. Conclusion MRI is particularly useful in cases where US is inconclusive and to assess the extent to which the placenta penetrates the uterine serosa and invades outward into surrounding tissues.MRI has become a routine examination for patients with suspected PA in clinical practice.
Keywords: Morbidity